Geo– . Geografia. Dzień geografa – mapa wizerunkiem świata. Geo-. Geography. Day of the geographer - map image of the world - Harłoziński, Kazimierz; Dorożyński, Ryszard (Journal of Education, Health and Sport, 2015)
Harłoziński Kazimierz, Dorożyński Ryszard. Geo– . Geografia. Dzień geografa – mapa wizerunkiem świata. Geo-. Geography. Day of the geographer - map image of the world. Journal of Education, Health and Sport. 2015;5(5):368-372. ISSN 2391-8306. DOI 10.5281/zenodo.17889 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A368-372 https://pbn.nauka.gov.pl/works/561526 http://dx.doi.org/10.5281/zenodo.17889 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.04.2015. Revised 18.05.2015. Accepted: 23.05.2015. GEO- GEOGRAFIA DZIEŃ GEOGRAFA – MAPA WIZERUNKIEM ŚWIATA Geo-. Geography. Day of the geographer - map image of the world Kazimierz Harłoziński, Ryszard Dorożyński Instytut Geografii, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Geografia ma przedrostek geo- co oznacza, że to dziedzina nauki i praktyki związana genetycznie z Ziemią. Współcześnie dysponuje Ona wiąż doskonalonym zasobem narzędzi badawczych i technologii opracowywania danych. Mogą one dostarczać wiele pakietów różnorodnych informacji o analizowanej przestrzeni w czasie rzeczywistym. Mapa jest wizerunkiem świata, jest również zwierciadłem dziejów ludzkości. Język graficzny mapy to uniwersalny nośnik danych o przestrzeni geograficznej. Ma niewątpliwą zaletę, a mianowicie, jest zrozumiały przez wszystkich ludzi bez względu na język jakim się oni posługują. Słowa kluczowe: Ziemia, przestrzeń, geografia, mapa, kartografia, teledetekcja, GIS, skala, współrzędne, nawigacja. Abstract Geography has the prefix geo- which means that it’s science and practice related genetically to the ground. Today it has a bind developing research tools resource and technology development of data. They can provide many packages a wide variety of information about the space in real time. The map is a picture of the world, it is also a reflection of the history of mankind. The graphic language of maps is a universal medium of geographical space. Has the undoubted advantage, namely, it is understood by all people, regardless of what language they speak. Keywords: Earth, space, geography, map, mapping, remote sensing, GIS, scale, coordinates navigation.